STRATEGI MENINGKATKAN MUTU PENDIDIKAN DI PERGURUAN TINGGI - Madinah, Sofyan (Hunafa: Jurnal Studia Islamika, 2006)
Enhancing skill to manage and to develop university is urgently needed, including the adoption of modern managerial principles  oriented  to quality. To managers of university, quality management system is  based on the ongoing improvement to strengthen and to improve. Monetary crises and free market have urged us to be more capable in deciding the future based on SWOT analyses. Kata Kunci : Strategi, mutu, pendidikan, perguruan tinggi